(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
Reducing the excessive heat from an engine is very crucial to avoid the damaging & overheating of the engine parts. Various methods used earlier include; using a radiator which has its own advantages and limitations. The micro heat exchangers has evolved as an efficient alternating method for heat removal from engine, The paper reviews research work carried out in the recent times to minimize heat from an engine at certain level, by using different methods.